Burden and causes of pregnancy-related mortality in The Gambia: evidence from census and health and demographic surveillance data - Georges Reniers; Mustapha Bittaye; Nuredin I Mohammed; Martin Antonio; Momodou Jasseh; Nyakassi Sanyang; Ursula Maria Gazeley (BMJ Publishing Group, 2023)
Background The Gambia lacks capacity to estimate its burden and causes of pregnancy-related mortality (PRM) to guide reproductive health programming. We used census and Health and Demographic Surveillance System (HDSS) data from Farafenni and Basse to establish levels and causes of PRM in The Gambia.Methods Using reported deaths and births in the 2013 Gambian census, national and regional pregnancy-related mortality ratios (PRMRatios) were derived as the ratio of pregnancy-related deaths (PRDs) per 100 000 live births (lbs). Verbal autopsies were interpreted using InterVA-5, and PRDs linked with extracted HDSS data to estimate annual PRMRatios.Results The census yielded national PRMRatio of 861 per 100 000 lbs in 2012. Regional levels of 1877, 1232 and 1096 per 100 000 lbs were registered in rural regions of Kuntaur, Mansakonko and Basse, respectively; while urban areas of Banjul and Kanifing registered about half these levels. Women aged 15-19 and 40-49 had greater risks of dying from pregnancy-related causes. HDSS data produced lower PRMRatios (95% CI) ranging from 858 per 100 000 lbs (149-4969) for Farafenni in 2005, and 479 per 100 000 lbs (328-698) for Basse in 2008 to 184 (24-1450) and 173 (61-487) per 100 000 lbs, respectively. InterVA-5 returned pregnancy-induced hypertension and obstetric haemorrhage as the main causes, accounting for at least 70% of all PRDs.Conclusion The census-based PRMRatios for 2012 were consistent with the sociodemographic and reproductive health indicators that prevailed at that time and represented the burden of PRM. While HDSS-derived PRMRatios were lower, the cause-of-death distribution produced was consistent with previous observations elsewhere.